Market integration and resident health in China - Feini Liu; Qing Yang; Tianlu Zheng; Xiang Li (Scientific Reports)
Abstract This paper uses data from the China Health and Nutrition Survey (CHNS) to study the impact of market integration on residents’ health. The empirical results based on the probit model show that market integration has a significant dampening effect on resident incidence. For every one-unit increase in the degree of market integration, the probability of residents becoming sick decreases by approximately 1.45%. Moreover, after a series of robustness tests, the conclusion is still valid. This study further analyses the potential mechanism and finds that the promotion of market integration can improve the medical conditions available to residents, optimize the nutritional indices of residents, and reduce labor load of residents, thus improving their health. The results of the heterogeneity test show that there are certain differences in the impact of market integration on the health level of residents of different genders, ages and income classes. At the same time, this study also verifies that there is a synergistic effect between internet penetration and market integration.